Spatial Analysis for Radar Remote Sensing of Tropical Forests. - De Grandi, G. F. (Gianfranco); De Grandi, Elsa Carla ([Place of publication not identified] : CRC Press, 2021)
Spatial Analysis for Radar Remote Sensing of Tropical Forests is based on the authors' extensive involvement in Synthetic Aperture Radar (SAR) mapping projects, targeting the health of an earth ecosystem with great relevance for climate change studies: the tropical forests. The subject is developed from a vantage point provided by analysis in a combined space, scale (frequency), time, wavelength, polarization domain. The combination of space and scale offers the capability to zoom in and out like a virtual microscope to the resolution in tune with the underlying ecological phenomenon. It also enables statistical measures (correlations) related to the forest spatial distribution in case of backscatter, or to the canopy height variations in case of interferometric observations. The time dimension brings into play measures of the ecosystem dynamics, such as the flooding extent in the swamp forests, deforestation or degradation events. Wavelength and polarization agility extend the abovementioned capabilities by radar observations that are in tune with particular characteristics of the forest and terrain layers. The book's spotlight is on radar spatial random fields, these being populated by either backscatter observations or elevation data from interferometric SAR. The basic tenet here is that the spatial statistic of the fields measured by the wavelet variance (in stationary or non-stationary situations) carries fingerprints of the forest structure. Features: Uniquely focused on specific techniques that provide multi-resolution spatial and temporal analysis of forest structure characteristics and changes. Examines several large and important international remote sensing projects aimed at documenting entire tropical ecosystems. Provides novel wavelet methods for tropical forest structural measures. As the first book on this topic, this composite approach appeals to both students learning through important case studies and to researchers finding new ideas for future studies.
PART I - SARCHEOLOGY: The Era of the big Radar Mosaics.The Dawn of The Radar Mosaics Era: The ESA-JRC Central Africa Mosaic Project. The L-Band Breed: The GRFM Africa Radar Mosaic. The CAMP-GRFM Thematic Products. Evolution of The Species: The ALOS PALSAR Africa Mosaic.PART II - Measures of SAR Random Fields in the Scale-Space-Time Domain.The Stuff Backscatter Random Fields are Made of. Statistical Measures of SAR Random Spatial Fields: Fingerprints of Forest Structure. Hitting Corners: The Lipschitz Regularity, a Measure of Discontinuities in Radar Images Connected with Forest Spatial Distribution. The Beauty Farm: A Wavelet Method for Edge Preserving Piece-Wise Smooth Approximations Of Radar Images. The Cleaning Service: A Multi-Temporal Insar Coherence Magnitude Filter. Proxies of Forest Volume Loss and Gain by Differencing Insar Dsms: Fingerprints Of Forest Disturbance.
OCLC-licensed vendor bibliographic record.
Keywords: Rain forests -- Remote sensing; Synthetic aperture radar; Forest surveys -- Data processing; Spatial analysis (Statistics)